2018
DOI: 10.31024/ajpp.2019.5.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some chloro-substituted isoxazoline derivatives as antibacterial agents

Abstract: Objectives: The chemistry of chalcones has generated intensive scientific studies throughout the world. Especially interest has been focused on the synthesis and biodynamic activities of isoxazoline derivatives. In recent year numerous isoxazoline derivatives have been synthesized for their anticancer, anti-inflammatory, cytotoxic, antiviral activities. The reaction of substituted chalcones with hydroxylamine hydrochloride in presence of acetic acid gave isoxazoline derivatives. : The five membered oxygen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These isoxazoline derivatives 91 a-f (Figure 15) were reported by Deshmukh et al and studied for antibacterial activities. [140] The synthesized isoxazoline derivatives, and demonstrated 91 a-d strong antibacterial activity against all the investigated species according to the screening experiments. The study found that electronrich 91 c, with one -OMe and two -Cl substituents, showed the best activity comparable to standard medication, supporting the hypothesis that isoxazolines with electrons have greater action.…”
Section: Antibacterialsmentioning
confidence: 97%
See 1 more Smart Citation
“…These isoxazoline derivatives 91 a-f (Figure 15) were reported by Deshmukh et al and studied for antibacterial activities. [140] The synthesized isoxazoline derivatives, and demonstrated 91 a-d strong antibacterial activity against all the investigated species according to the screening experiments. The study found that electronrich 91 c, with one -OMe and two -Cl substituents, showed the best activity comparable to standard medication, supporting the hypothesis that isoxazolines with electrons have greater action.…”
Section: Antibacterialsmentioning
confidence: 97%
“…These isoxazoline derivatives 91 a – f (Figure 15) were reported by Deshmukh et al . and studied for antibacterial activities [140] . The synthesized isoxazoline derivatives, and demonstrated 91 a – d strong antibacterial activity against all the investigated species according to the screening experiments.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…as they assayed the synthesized compounds against Gram‐positive and Gram‐negative strains. Among the synthesized analogues, compound 73 was found to be potent with MIC values of 26–28 μM relative to the standard drug ofloxacin [142] . A metal‐free method with assistance from potassium iodate (KIO 3 ) was generated by Kotian et al.…”
Section: Pharmacological Profile Of Isoxazoline Derivativesmentioning
confidence: 99%
“…Isoxazole/isoxazoline is a vital N- and O-containing heterocyclic molecule with a five-membered ring and is found throughout natural products . It has been employed extensively in drug discovery because of their potent antimicrobial, fungicidal, , and insecticidal properties. , Many products derived from these structures, such as fluralaner and afoxolaner, are commercially available. , In this study, isoxazole and isoxazoline were introduced into the 3-position benzene ring of pyrido­[1,2- a ]­pyrimidinone (Figure ) and a series of novel pyrido­[1,2- a ]­pyrimidinone compounds was synthesized. The insecticidal activity of the target compounds against A.…”
Section: Introductionmentioning
confidence: 99%
“…27 Isoxazole/isoxazoline is a vital N-and O-containing heterocyclic molecule with a five-membered ring and is found throughout natural products. 28 It has been employed extensively in drug discovery because of their potent antimicrobial, 29 fungicidal, 30,31 and insecticidal properties. 32,33 Many products derived from these structures, such as fluralaner and afoxolaner, are commercially available.…”
Section: ■ Introductionmentioning
confidence: 99%